Utilization of Palm Oil Mill Residue as Sustainable Pavement Materials: A Review - Yaro, N.S.A. (Penerbit UTHM, 2021)
The advances in industrial technology have led to a major rise in the amount and forms of residue, especially during the processing of agricultural products. With the paradigm shift towards renewable energy and sustainability, there is much emphasis on biomass energy around the world which generates an immense volume of residues yearly. These residues are burgeoning issues because they are not effectively managed and utilized. Hence, one solution is utilizing them in the pavement industry. This article focuses on palm oil mill residues that are abundantly available and discarded in Malaysia. This study evaluates published works of literature relating to the utilization of these residues like the Palm Oil Fiber (POF), Palm Oil Fuel Ash (POFA), and Palm Oil Clinker (POC) and Palm Kernel Shell (PKS) in the pavement industry. The outcome of the review acknowledges the greater sustainability potential of these residues with affirmative and satisfactory performance via the result of numerous research work. Also, with a reduction in CO2-emission, low radioactivity, and heavy metal leaching level. Therefore, the review suggests more exploration and utilization of the residue in the pavement industry since it promotes safety and harness sustainability. Â© Universiti Tun Hussein Onn Malaysia Publisherâs Office